براہوئی زبان ٹی اصطلاح سازی: Study of Terminology in Brahui Language - Murad, Afzal (Al-Burz, 2013)
This scholarly article reflects the terminological deficiency of Brahui language. Due to such linguistics institution and learned scholar Brahui language has been shifting and taking barrowed from English, Urdu, Sindhi, Pashto and Balochi. Department of Brahui can initiate a step or institution in the supervision of Dr.Liaqat Sani to resolve terminological issues in Brahui. With the passage of time literature and Language needs promotion in its self. This article may cause to commence an idea to make consensus about to resolve Brahui lingual issues.